ADAPTATION OF MARKETING COMPLEX OF UZBEKISTAN EXPORT-ORIENTED ENTERPRISES TO REGIONAL MARKETS (Marketing Journal, 2026)
This article examines the peculiarities of adapting marketing complex elements (product, price, distribution, promotion) by Uzbekistanʼs enterprises to effectively enter the markets of the SCO and CIS countries, which are priority areas within regional eco nomic integration, and strengthen their positions. Such problems as the need for deep product modification in accordance with the standards of the Eurasian Economic Union, high dependence of prices on logistics costs, vulnerability of own distribution channels, and low efficiency of digital promotion in th e Chinese market were identified. Differentiated strategies have been defined for the CIS (with an emphasis on cultural proximity) and China (with an emphasis on digitalization and working through platforms) markets. Successful adaptation to 4P requires Uz bekistanʼs enterprises to shift from excess product export tactics to targeted marketing strategy focused on specific consumers in each partner country, establish joint ventures to overcome non -tariff barriers, and actively utilize regional trade agreement tools.
Keywords: 4P marketing complex; export; import; foreign economic activity; SCO; CIS; regional integration; product adaptation; price adaptation; sales promotion